The Restoration Effect of Degraded Grassland Depends on the Response of Species Root Distribution to Resource Availability - Yiming Zhao; Hui Li; Fei Peng; Dabu Xilatu; Qing Chen; Shan Lin (Agronomy)
Nitrogen (N) fertilization is an effective practice for restoring degraded grasslands, which might strongly depend on the rooting system and resource competition of individual plant species. The purpose of this study is to explore a method to distinguish the response of various plant root architectures to the resource availability in a mixed ecosystem in situ. Field experiments were conducted using isotope techniques in conjunction with a specialized experimental design at a semiarid grassland location featuring heavily grazed (HG) and moderately grazed (MG) grassland sites with different dominant species. The same amounts of water and 15N-labelled fertilizer were uniformly supplied by a tube fertigation system at soil depths of 0, 15 and 45 cm. At both the HG and MG sites, there was a significant increase in aboveground net primary production (ANPP), water use efficiency (WUE) and 15N use efficiency (15NUE) at the community level with increasing depths of fertigation. The ANPP and plant N uptake exhibited higher values at the HG site compared to those at the MG site, while 15NUE and 15N abundance were significantly lower at the HG site. The annual species Salsola collina Pall. exhibited the highest aboveground biomass (AGB) and 15N abundance compared to all other species. Furthermore, the 15N enrichment of S. collina increased with greater depths of 15N-labelled fertilization, indicating that S. collina might develop a more extensive root system in response to water and N addition in the degraded grassland. Our study highlights that using isotope methods could indirectly distinguish root distribution and resource acquisition. In the recovery of degraded grassland by N fertilizer, we should not only consider the aboveground biomass but also pay special attention to the resource competition of individual plant species due to the possible discrepancy in rooting systems.